2008
DOI: 10.2146/ajhp080168
|View full text |Cite
|
Sign up to set email alerts
|

Update on cardiopulmonary resuscitation and emergency cardiovascular care guidelines

Abstract: Several evidence-based changes were included in the 2005 CPR and ECC guidelines, including a C:V ratio of 30:2 and mitigation of hands-off time, early defibrillation, administration of a single shock versus a three-shock sequence, use of public-access defibrillators, and a shift from primary-rhythm-based therapies to a focus on neurologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 107 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…Despite scientific progress and supports of Global Health Systems, the outcome of SCA victims still remains quite poor due to the inadequate perfusion of vital organs during CPR [25,26]. As a result, more than half of postresuscitation syndrome deaths occur within 24 h after the return of spontaneous circulation (ROSC), due to multiple organs failure and about 2% of the victims may survive without brain damage the first year postarrest [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Despite scientific progress and supports of Global Health Systems, the outcome of SCA victims still remains quite poor due to the inadequate perfusion of vital organs during CPR [25,26]. As a result, more than half of postresuscitation syndrome deaths occur within 24 h after the return of spontaneous circulation (ROSC), due to multiple organs failure and about 2% of the victims may survive without brain damage the first year postarrest [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The success rate of administering an electric shock as part of CPR within 1 minute of a sudden cardiac arrest caused by an arrhythmia is over 90%, but the success rate falls by 7% to 10% per minute after. [3] Previous studies had revealed that effective bystander CPR can significant improve pre-hospital mortality rate. [47]…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, rate of survival to hospital discharge (STD) ranged from 4% to 9% worldwide. 1 However, for those presented with non-shockable rhythm, only 1% to 4% survived.…”
Section: Introductionmentioning
confidence: 99%